Discursive "Renovatio" in Lope de Vega and Calderón. Studies on Spanish Baroque Drama - Küpper, Joachim (De Gruyter, 2017)
This volume offers a fresh look at Spanish Baroque drama (centered on readings of plays by Lope de Vega and Calderón) inspired by Foucault's discourse archeology. This perspective implies a discussion of the plays' discourse-historical "foils" and of related (theological, philosophical, and historiographical) discourses. A separate "excursus" discusses the discursive relation between the Middle Ages, the Renaissance, Mannerism and the Baroque.